International Skilled Labour Migration Flows Into Malaysia And Its Impact On Malaysian Economy - tan, Chuie Hong (2008)
International migration of the skilled labour has existed for decades as a mean of circulating knowledge, promoting scientific andtechnological development. The objective of this study are (1) to study the trends of skilled labour immigration into Malaysia during 1998-2004; (2) to analyse the macroeconomic determinants of skilled labour immigration into Malaysia during the period 1998-2004; (3) to study the impact of skilled labour immigrants on Malaysia trade flows and identify underlying mechanisms underpinning this relationship; (4) to analyse the association between Malaysia foreign direct investment and its skilled labour immigration; (5) to gauge the perceptions and well-being of expatriates to Malaysia in terms of economy, society and culture.